NEO-SUFI REFLECTIONS IN SOHRAB SEPEHRI’S POETRY (Journal of Oriental Studies, 2025)
This article examines the poetic development of modern Persian poet Sohrab Sepehri as a manifestation of neo-mystical thought. It analyzes the religious and philosophical traditions that influenced his work, including Sufism, pantheism, Buddhism, and elements of Western mysticism. The author demonstrates how Sepehri, drawing on classical models of spiritual transformation, created a distinctive poetic language rich in symbolism. The analysis reveals how Sepehri’s personal spiritual experience evolves into a universal mystical system, reflecting his effort to synthesize Eastern and Western philosophical traditions.
Keywords: Sohrab Sepehri; neo-mysticism; Persian poetry; mysticism; symbols; spiritual journey